Diversity in information technology education issues and controversies - Trajkovski, Goran P. 1972-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
This book investigates the status of diversity in the field of IT education with research on racial, gender, national origin, disability and other diversity categories.
Electronic reproduction.
Keywords: Information technology -- Study and teaching; Multicultural education -- United States; Electronic books